2004
DOI: 10.1385/ct:4:2:133
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Mitochondrial Toxicity in Hearts of Female B6C3F1 Mice Exposed <I> In Utero</I> to 3'-Azido-3'-Deoxythymidine

Abstract: Cardiac toxicity has been associated with HIV infection and exposure to nucleoside reverse transcriptase inhibitors (NRTIs), but the role of the latter in the development of cardiac disease of HIV-infected patients is uncertain. To investigate the cardiotoxicity of transplacentally administered zidovudine (AZT) or AZT plus lamivudine (3TC) in the absence of HIV infection, we evaluated several biomarkers of cardiac mitochondrial structure and cardiac structure and function in a B6C3F1 mouse model. In utero expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 33 publications
4
46
0
Order By: Relevance
“…Despite the past routine usage of AZT in mothers and the continuing use in neonates, the metabolism and mechanism(s) of toxicity of AZT or other analogues in the NRTI group have been poorly studied in neonates. Past studies have shown mitochondrial DNA depletion involving adult rat or mouse populations when treated with oral AZT (15,16,32). Our data show for the first time that AZT dramatically altered the size and composition of the dNTP pools during early neonatal growth (Fig.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Despite the past routine usage of AZT in mothers and the continuing use in neonates, the metabolism and mechanism(s) of toxicity of AZT or other analogues in the NRTI group have been poorly studied in neonates. Past studies have shown mitochondrial DNA depletion involving adult rat or mouse populations when treated with oral AZT (15,16,32). Our data show for the first time that AZT dramatically altered the size and composition of the dNTP pools during early neonatal growth (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Shortterm (7)(8)(9)(10)(11)(12)(13)(14) and long-term (15)(16)(17)(18) problems associated with AZT treatment in neonatal animal models and humans have been noted by others and are described in the introduction. It has been previously shown that alterations in dNTP composition are associated with mutagenesis in nuclear and mitochondrial DNA (23,26) and may account for the long-term problems (15)(16)(17)(18) and reports of AZT-induced carcinogenicity (15). While not a goal of this study, an examination of the implications of the AZT-induced cellular changes noted here on both short-term and long-term health of the animals is planned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, ageing is also contributed by deficit in mitochondrial energy as a result of depletion of mitochondrial DNA (Shigenaga et al, 1994). ZDV is a drug linked to transplacental mitochondrial dysfunction in humans (Blanche et al, 1999;Poirier et al, 2003;Venhoff and Walker, 2006), in animal experiments (Gerschenson et al, 2004;Walker et al, 2004) as well as in vitro study (Cazzalini et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, expanded use of multiple antiretroviral drugs during pregnancy has led to concerns regarding both short-term toxicities and long-term health risks to the drug-exposed infants, almost all of whom are born free of HIV-1-infection [Watts, 2006]. The theoretical longer-term effects, as evidenced in experimental models, include NRTI-induced carcinogenesis and mitochondrial abnormalities [Olivero et al, 1997;Diwan et al, 1999;Dagan et al, 2002;Poirier et al, 2004;Walker et al, 2004Walker et al, , 2007NTP, 2006], suggesting that monitoring of children exposed perinatally to antiretrovirals be recommended in order to intervene should adverse outcomes appear [Watts, 2006].…”
mentioning
confidence: 99%